2018
DOI: 10.1590/0034-7167-2017-0838
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and associated factors in young adult student girls

Abstract: Objective: To analyze overweight and associated factors in young adult student girls children in a capital city of Northeast Brazil. Method: An analytical, quantitative study was conducted with 546 young adults from 26 schools in a capital city of the Brazilian Northeast. After obtaining the data by the application of a specific questionnaire, the hierarchical logistic regression was used to identify the confounding variables and predictors of overweight. Results: The frequency of cases of overweight in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…Menarche before the age of 12 represented a factor positively associated with excess weight, corroborating other studies (7,30,35,36) . A study with 400 Indian women, signaled that the majority with early menarche had, showed higher adiposity markers such as BMI, waist hip ratio, waist height ratio and waist circumference.…”
Section: Factors Associated and Obesity/overweightsupporting
confidence: 91%
“…Menarche before the age of 12 represented a factor positively associated with excess weight, corroborating other studies (7,30,35,36) . A study with 400 Indian women, signaled that the majority with early menarche had, showed higher adiposity markers such as BMI, waist hip ratio, waist height ratio and waist circumference.…”
Section: Factors Associated and Obesity/overweightsupporting
confidence: 91%
“…(Sousa e Barbosa, 2017;Vigitel Brasil, 2018). Ademais, o sobrepeso e a obesidade apresentaram relação direta com a idade, evidenciando o início nesse período da vida e acompanhando a mudança de faixa etária (Costa et al, 2018;Silva et al, 2020).…”
Section: Questionário Findrisc Como Ferramenta Para O Risco De Dm2unclassified